Integrating Science and Religion through Academic Writing: A Case Study at MAN Insan Cendekia - Riwanda, Agus; Huda, Hisbullah; Nadlir, Nadlir; Yani, Achmad (Badan Litbang dan Diklat Kementerian Agama RI, 2024)
The Indonesian Ministry of Religious Affairs has emphasized the integration of science and religion within madrasah education to improve graduate quality. MAN Insan Cendekia has been at the forefront of this initiative, aiming to enhance student literacy and methodological rigor through academic writing programs. This study aims to evaluate the implementation and impact of the academic writing program at MAN IC Tanah Laut, focusing on how it integrates science and religion through a multidisciplinary approach. Employing a case study approach, the research involved data collection from the madrasah headmaster, deputy academic, academic writing program coordinators, and supervising teachers. Data analysis was conducted using the Miles and Huberman model, which includes data condensation, display, and conclusion drawing. The academic writing program at MAN IC Tanah Laut began in 2016 as an extracurricular activity, requiring all students to participate and be guided by teachers in researching contemporary issues from various disciplinary perspectives. By 2018, it had become a co-curricular flagship initiative and was integrated into the core curriculum as a graduation requirement for grade XII by 2021. The program's evolution contributed significantly to the school’s achievements, including securing a second runner-up position in the MYRES competition in 2021 and winning a championship in the field of religion with a scientific emphasis in 2022. These outcomes demonstrate the program's success in effectively blending scientific and religious education. The research underscores the necessity of designing holistic curricula that foster interdisciplinary learning. It highlights the importance of enhancing methodological quality in academic writing programs, investing in teacher development, implementing authentic assessment models, and engaging the community. These findings offer valuable insights for other madrasahs and religious institutions aiming to integrate science and religion in their educational frameworks.